2021
DOI: 10.1093/heapol/czab091
|View full text |Cite
|
Sign up to set email alerts
|

Health and politics in pandemic times: COVID-19 responses in Ethiopia

Abstract: With a focus on responses to coronavirus disease 2019 (COVID-19) in Ethiopia and on political developments that have occurred in the country during the pandemic, this article contributes to the existing scholarship that explores the relationship between health and politics. Drawing on qualitative data from the project ‘COVID-19 Impact Tracing in Ethiopia: Social, Economic, Political, and Security Ramifications’, carried out in the Tigray, Amhara and Oromia Regional States (RS) from June to September 2020, we o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
(24 reference statements)
1
7
0
Order By: Relevance
“…However, government pandemic management was inconsistent in 2020 and 2021 due to government instability, as well as low levels of public trust, coupled by reduced willingness to enact unpopular lockdowns close to parliamentary election [ 49 ]. Government instability and low trust in government have also made it difficult for other low- and middle-income countries to manage a pandemic [ 70 ]. According to the analysis of Badman and colleagues, trust in national and local public health institutions needs to be developed to increase the population’s willingness to cooperate with non-pharmaceutical measures.…”
Section: Discussionmentioning
confidence: 99%
“…However, government pandemic management was inconsistent in 2020 and 2021 due to government instability, as well as low levels of public trust, coupled by reduced willingness to enact unpopular lockdowns close to parliamentary election [ 49 ]. Government instability and low trust in government have also made it difficult for other low- and middle-income countries to manage a pandemic [ 70 ]. According to the analysis of Badman and colleagues, trust in national and local public health institutions needs to be developed to increase the population’s willingness to cooperate with non-pharmaceutical measures.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have revealed that public health policies and systems appear to be built loosely on technical and scientific evidence, but with high political systems and ideologies [ 13 16 ]. For instance, in most African countries such as Ghana, Kenya, Nigeria, South Africa, Tunisia, and Zimbabwe, the management of the novel SARS-CoV-2 pandemic and the public health response have been heavily politicized [ 16 – 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that public health policies and systems appear to be built loosely on technical and scientific evidence, but with high political systems and ideologies [ 13 16 ]. For instance, in most African countries such as Ghana, Kenya, Nigeria, South Africa, Tunisia, and Zimbabwe, the management of the novel SARS-CoV-2 pandemic and the public health response have been heavily politicized [ 16 – 18 ]. Regardless of the seeming increase in research evidence on the central role of political leadership in defining national public health policies in Africa, there seems to be inadequate empirical accounts of the common themes or concepts in the existing literature regarding the politics–evidence conflict in the public health policy-making process [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since November 4, 2020 war has been started following Ethiopian Northern Command attack by Tigray People Libration Front (TPLF). A millions were displaced, thousands massacred, all public and private infrastructures destroyed in the conflict setting, children were raped in group, thousands killed [3,4]. This in turn highly influences the mental well-being of conflict-affected people in Ethiopia during COVID-19 era.…”
Section: Introductionmentioning
confidence: 99%